Alternative polyadenylation and the stress response. (2nd May 2019) - Sadek, Jason; Omer, Amr; Hall, Derek; Ashour, Kholoud; Gallouzi, Imed Eddine
Abstract: The cellular stress response is a universal mechanism necessary for the survival of all organisms. This multifaceted process is primarily driven by regulation of gene expression to produce an intracellular environment suitable for promoting cell survival and recovery. Posttranscriptional regulatory events are considered as critical mechanisms that modulate core characteristics of mRNA transcripts to promote cell adaptation to various assaults. While the impact of processes such as mRNA splicing, turnover, localization, and translation on the cellular stress response has been extensively studied, recent observations highlight the role of alternative polyadenylation (APA) in response to challenges such as oxidative stress, heat shock, and starvation. The role of APA is comprehensive with far reaching effects on mRNA stability, mRNA localization, and protein coding sequences. Nonetheless, APA remains a relatively unappreciated mode of gene regulation despite its role in regulating key mediators of the stress response. The goal of this review is to provide an overview of the recent advances in our understanding of the various ways by which APA affects cell adaptation to its environment and discuss how a defect in APA could have deleterious consequences on cell survival. This article is categorized under: RNA in Disease and Development > RNA in Disease RNA Structure and Dynamics > Influence of RNA Structure in Biological Systems RNA Processing > 3′ End Processing Abstract : Various stresses induce alternative polyadenylation of nascent transcripts modulating their temporospatial expression. In turn, these transcripts produce the factors necessary for the cellular adaption to external and internal assaults.